2016
DOI: 10.4088/jcp.14m09394
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Serotonin-Norepinephrine Reuptake Inhibitors Versus Selective Serotonin Reuptake Inhibitors on Cerebrovascular Events

Abstract: Use of SNRIs is not associated with an increased risk of either ischemic stroke or intracranial hemorrhage as compared to use of SSRIs in adult patients with depression or anxiety. However, SNRIs should be used cautiously in patients without depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…We compare our approach to a previously published study by Lee et al . [ 18 ]. Whereas that study compares new users of the entire drug classes to which these drugs belong, our analysis investigates new users of the two specific drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compare our approach to a previously published study by Lee et al . [ 18 ]. Whereas that study compares new users of the entire drug classes to which these drugs belong, our analysis investigates new users of the two specific drugs.…”
Section: Resultsmentioning
confidence: 99%
“…This result stands agreement with Lee et al . [ 18 ], who included 76 920 new users of the class containing duloxetine and 582 650 new users of the class containing sertraline, and reports an adjusted hazard ratio of 1.01 (95% CI: 0.90–1.12). Both studies also include sensitivity analyses that consider an alternative time-at-risk definition and show little variation in the estimate.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis focused exclusively on the risk of SDH associated with antidepressant use has not previously been published. Other factors further complicate comparisons with previous results, as emphasized in a recent systematic review of 12 studies, which reported substantial heterogeneity with regard to design . However, two previous studies were noted for their large size and lack of major methodological limitations .…”
Section: Discussionmentioning
confidence: 96%
“…Selective serotonin reuptake inhibitors (SSRIs) are frequently used to treat depression and other psychiatric disorders and have been suspected of increasing the risk of bleeds through mechanisms affecting platelet function . Several studies of SSRI use as a risk factor for severe bleeds have been published, including studies of intracranial hemorrhage . However, in most studies, different intracranial bleed events have been pooled, a practice criticized by some, as it may conceal effects particular to one type of bleed .…”
Section: Introductionmentioning
confidence: 99%
“…As a secondary mechanism of action, SSRIs increase efficacy of 5-hydroxytryptamine (5-HT) neurons by desensitizing 5-HT autoreceptors of the serotonin nerve terminals. 4 , 5) …”
Section: Introductionmentioning
confidence: 99%